2012
DOI: 10.1152/ajplung.00303.2011
|View full text |Cite
|
Sign up to set email alerts
|

Activity and inhibition of prostasin and matriptase on apical and basolateral surfaces of human airway epithelial cells

Abstract: Nimishakavi S, Besprozvannaya M, Raymond WW, Craik CS, Gruenert DC, Caughey GH. Activity and inhibition of prostasin and matriptase on apical and basolateral surfaces of human airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
4
19
0
1
Order By: Relevance
“…As shown in Fig. 4A, this substrate is selective for mouse marapsin over mouse prostasin, whereas commercially available substrate QAR-4NA (which is a substrate for human prostasin and detects prostasin and matriptase activity in cultured cells (31)) was preferred by mouse prostasin.…”
Section: A Tetrapeptide Substrate Based On Marapsin Cleavage Preferenmentioning
confidence: 97%
“…As shown in Fig. 4A, this substrate is selective for mouse marapsin over mouse prostasin, whereas commercially available substrate QAR-4NA (which is a substrate for human prostasin and detects prostasin and matriptase activity in cultured cells (31)) was preferred by mouse prostasin.…”
Section: A Tetrapeptide Substrate Based On Marapsin Cleavage Preferenmentioning
confidence: 97%
“…Indeed, a point mutation introduced in the catalytic triad confirmed that the proteolytic activation of HAT requires serine protease activity in transfected human embryonic kidney cells 293 (HEK293 cells) (60). Whether HAT can activate other TTSPs is still underexplored, but this is highly likely since activation of family members has been described for other members of the family (99,116).…”
Section: Hat: Structure Catalytic Activity and Regulationmentioning
confidence: 99%
“…Serine proteinases expressed by epithelial cells (prostasin 58 ) or PMNs (NE 59 ), and acidic proteinases expressed by macrophages and epithelial cells (cathepsins B and S 60,61 ) proteolytically activate airway ENaC to increase sodium hyperabsorption and ASL dehydration. However, to date, there are no reports in the literature that MMPs proteolytically regulate ENaC or other sodium channels in the airway epithelium.…”
Section: Cftr and Mmpsmentioning
confidence: 99%